2023
DOI: 10.1186/s12885-023-10648-1
|View full text |Cite
|
Sign up to set email alerts
|

Colposcopic accuracy in diagnosing squamous intraepithelial lesions: a systematic review and meta-analysis of the International Federation of Cervical Pathology and Colposcopy 2011 terminology

Abstract: Background Colposcopy is an important tool in diagnosing cervical cancer, and the International Federation of Cervical Pathology and Colposcopy (IFCPC) issued the latest version of the guidelines in 2011. This study aims to systematically assess the accuracy of colposcopy in predicting low-grade squamous intraepithelial lesions or worse (LSIL+) / high-grade squamous intraepithelial lesions or worse (HSIL+) under the 2011 IFCPC terminology. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 47 publications
0
7
0
1
Order By: Relevance
“…In a study also done in China, the sensitivity, specificity, and accuracy of colposcopy to diagnose histologic CIN2 + were 70.2%, 75.1% and 72.9%, respectively [ 16 ]. A recent meta-analysis showed that colposcopic accuracy for detecting CIN2 + was 89%, with combined sensitivity and specificity were 68% and 93%, respectively [ 28 ]. The sensitivity of colposcopic impressions ranged from 29 to 100% and the specificity from 12 to 88% based on 11 studies [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a study also done in China, the sensitivity, specificity, and accuracy of colposcopy to diagnose histologic CIN2 + were 70.2%, 75.1% and 72.9%, respectively [ 16 ]. A recent meta-analysis showed that colposcopic accuracy for detecting CIN2 + was 89%, with combined sensitivity and specificity were 68% and 93%, respectively [ 28 ]. The sensitivity of colposcopic impressions ranged from 29 to 100% and the specificity from 12 to 88% based on 11 studies [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Improving the accuracy of colposcopy is the most important factor in early detection of cervical cancer. Even for experienced colposcopists, there can be errors in accurate diagnosis through colposcopy 28 , 29 . The role of cervical cancer screening through CerviCARE AI has become more important recently.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that colposcopic diagnosis often underestimates [ 31 ] or overestimates [ 34 ] in predicting squamous intraepithelial lesions. Recently, a systematic review and meta-analysis showed that the overall accuracy was 89% when using colposcopy to detect CIN2+, with combined sensitivity and specificity 68% and 93%, respectively [ 35 ]. Interestingly, they also demonstrated that colposcopy was more sensitive to low-grade squamous intraepithelial lesions or worse (LSIL+) and was more specific to CIN2+ [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a systematic review and meta-analysis showed that the overall accuracy was 89% when using colposcopy to detect CIN2+, with combined sensitivity and specificity 68% and 93%, respectively [ 35 ]. Interestingly, they also demonstrated that colposcopy was more sensitive to low-grade squamous intraepithelial lesions or worse (LSIL+) and was more specific to CIN2+ [ 35 ]. The sensitivity of colposcopic diagnosis ranged from 29 to 100% and the specificity from 12 to 88% based on 11 studies [ 36 ].…”
Section: Discussionmentioning
confidence: 99%